2019
DOI: 10.1111/conl.12667
|View full text |Cite
|
Sign up to set email alerts
|

First camera survey in Burkina Faso and Niger reveals human pressures on mammal communities within the largest protected area complex in West Africa

Abstract: The dearth of ecological data from protected areas at relevant scales challenges conservation practice in West Africa. We conducted the first camera survey for Burkina Faso and Niger to elucidate interactions between resource users and mammals in the largest protected area complex in West Africa (W‐Arly‐Pendjari, WAP). We differentiated direct (e.g., poaching) and indirect (e.g., domestic animals) human activities to determine their effects on species richness, composition, and behavior. Livestock was the domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Our specific study area, situated within WAP, included three NPs and 11 HCs in Burkina Faso and Niger (Figure 1). Five large predator species occur within WAP: lions Panthera leo, spotted hyenas Crocuta crocuta, leopards Panthera pardus, cheetahs Acinonyx jubatus and striped hyenas Hyaena hyaena, though cheetahs and striped hyenas are extremely rare in the system (only two and one detections in our survey, respectively; Harris et al, 2019;Lamarque, 2004). Potential prey items include olive baboons Papio anubis, aardvarks Orycteropus afer and many ungulate species common to West African savannas (see methods in Supporting Information Appendix S1).…”
Section: Study Areamentioning
confidence: 81%
See 1 more Smart Citation
“…Our specific study area, situated within WAP, included three NPs and 11 HCs in Burkina Faso and Niger (Figure 1). Five large predator species occur within WAP: lions Panthera leo, spotted hyenas Crocuta crocuta, leopards Panthera pardus, cheetahs Acinonyx jubatus and striped hyenas Hyaena hyaena, though cheetahs and striped hyenas are extremely rare in the system (only two and one detections in our survey, respectively; Harris et al, 2019;Lamarque, 2004). Potential prey items include olive baboons Papio anubis, aardvarks Orycteropus afer and many ungulate species common to West African savannas (see methods in Supporting Information Appendix S1).…”
Section: Study Areamentioning
confidence: 81%
“…Significance is indicated in the top middle of each individual plot. Significant differences between management types were tested using a Mann-Whitney U test for non-normally distributed data and t-test for only prey availability that was normally distributed (Shapiro-Wilk normality test p < 0.05) conservation in WAP would benefit from a study to evaluate the distribution of cause-specific mortality across management types, as human activities in WAP are varied and pose differential levels of risk but the propensity of lions to discriminate such threats remains unclear (Harris et al, 2019). In addition, future work would benefit from analyses of temporal partitioning and multi-species occupancy modelling to further examine lion responses to human pressures and coexistence dynamics in WAP where spatial avoidance is low (Carter et al, 2012; see Results for further consideration of fine-scale spatiotemporal partitioning, Appendix S1.)…”
Section: Discussionmentioning
confidence: 99%
“…In areas that have lost their natural herbivores, pastoralism further helps to keep the landscape open and hence to maintain biodiversity (Pykälä, 2000). However, pastoralism was recently linked to reduced activity of many mammals in Western Africa (Harris, 2019), and its impact on previously uninhabited regions is not well understood, particularly in the absence of strict conservation management.…”
Section: Introductionmentioning
confidence: 99%
“…Because we aggregated a variety of human activities to depict human use, there might be activity-specific responses by wildlife that were not captured. Humans exploit resources in national parks in many ways including livestock herding, resource gathering, subsistence poaching, hunting, and recreation, all of which impact the system and wildlife to varying degrees ( Everatt et al, 2019 ; Geldmann et al, 2019 ; Harris et al, 2019 ). Indeed, Harris et al, 2019 found differential impacts of human activities on wildlife behavior in WAP, suggesting species in this system do not respond to all humans uniformly.…”
Section: Discussionmentioning
confidence: 99%
“…Trophy hunting of many ungulate species and African lions ( Panthera leo ) is permitted in hunting concessions, while all hunting is illegal in the national parks and reserves in the complex. Other human activities in the park include livestock herding, resource extraction, recreation, and poaching ( Sogbohossou et al, 2011 ; Miller et al, 2015 ; Harris et al, 2019 ). Recently, Harris et al, 2019 reported 4 large carnivore species (African lion, African leopard Panthera pardus , spotted hyena Crocuta crocuta, and cheetah Acinonyx jubatus ) and 17 ungulate species belonging to the superorder Ungulata in the three national parks included in our study area from an extensive camera trap survey.…”
Section: Methodsmentioning
confidence: 99%